THE APPLICATION OF PROMOTION MIX IN INCREASING THE ROOM OCCUPANCY AT THE SAMAYA SEMINYAK - Ni Putu Dian Prabawati Devi; Budi Susanto; I Ketut Suarja; I Gusti Agus Mas Krisna Komala Sari (Politeknik Negeri Bali, 2018)
The purpose of this study is to determine the influence of promotion costs against occupancy rooms at The Samaya Seminyak. The data in this research is a secondary data regarding the cost of promotion and occupancy of the rooms at The Samaya Seminyak. Data analysis is simple regression analysis. The findings of this research is that the cost of promotion has positive and significant effect on room occupancy. Whereas, based on the results of the analysis of the coefficient of correlation and determination, the influence of promotion costs against occupancy rooms at The Samaya Seminyak is very strong, amounting to 68.6%, while the rest which amounts to 31.4% is influenced by other factors which is not examined in this study.